Penerapan Model Pembelajaran Inquiry Melalui Aplikasi Google Classroom Untuk Meningkatkan Hasil Belajar Mata Pelajaran Produk Kreatif dan Kewirausahaan Masa Pandemi Covid-19 Siswa Kelas Xi Tata Boga SMK Negeri 1 Dumai Tahun 2021 - Desriyul Fitri (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research was motivated by the low learning outcomes of students in the Creative Products and Entrepreneurship Subject during the Covid-19 Pandemic through the application of an inquiry learning model through the google classroom application for Class XI Culinary Planning Students at SMK Negeri 1 Dumai in 2021. The subjects in this study were class students The XI Culinary Administration of SMK Negeri 1 Dumai in 2021 has a total of 35 students. The tools to be used to collect data are observation sheets and tests. Observations were made to observe the activities of teachers and students in learning and tests were given to see the level of success of students from a teaching material delivered. Based on the results of the pretest student learning outcomes are still low. From the Minimum Completeness Criteria (KKM) set by the school, namely 75. Based on the results of the study, the following data were obtained: 1) The number of students' completeness before the action was 15 people or 37.5%, an increase in cycle I was 23 people or 65.71%. In cycle II there was also an increase of 29 people or 91.43%, 2) Student activity during the learning process also increased. In the first cycle of the first meeting, the average student activity was only 63.54%. At the second meeting it increased to 77.43%. In cycle II there was another increase, namely at the first meeting 88.89% increased at the second meeting to 94.09% with a very good category. So that the average student activity for the first cycle of 70.48% increased in the second cycle to 93.10% with a very good category, 3) Teacher activity during the learning process also increased. At the first meeting of cycle I, the total score of teacher activity was 39 (65%) increasing to 46 (76.67%) at the second meeting. Then it increased again to 53 (88.3%) at the first meeting and finally 60 (100%) at the second meeting. The results of the research generally show that the Application of the Inquiry Learning Model Through the Google Classroom Application can improve Learning Outcomes in the Subject of Creative Products and Entrepreneurship During the Covid-19 Pandemic for Class XI Culinary Planning Students at SMK Negeri 1 Dumai in 2021.